2021
DOI: 10.1155/2021/9954547
|View full text |Cite
|
Sign up to set email alerts
|

Increased Homotopic Connectivity in the Prefrontal Cortex Modulated by Olanzapine Predicts Therapeutic Efficacy in Patients with Schizophrenia

Abstract: Background. Previous studies have revealed the abnormalities in homotopic connectivity in schizophrenia. However, the relationship of these deficits to antipsychotic treatment in schizophrenia remains unclear. This study explored the effects of antipsychotic therapy on brain homotopic connectivity and whether the homotopic connectivity of these regions might predict individual treatment response in schizophrenic patients. Methods. A total of 21 schizophrenic patients and 20 healthy controls were scanned by the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(26 citation statements)
references
References 65 publications
2
24
0
Order By: Relevance
“…Therefore, DC and VMHC may be more appropriate than conventional FC in studying neuropsychiatric disorders whose pathological mechanisms were unclear ( Jiang et al., 2019 ). We found that DC and VMHC are physiologically meaningful and beneficial in understanding the underlying mechanism of SZ, DC- and VMHC-based features can distinguish SZ patients from HCs, in agreement with other studies ( de Filippis et al., 2019 ; Liu et al., 2018 ; Shan et al., 2021 ; Shi et al., 2021a ; Tang et al., 2019 ; Zang et al., 2021 ).…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…Therefore, DC and VMHC may be more appropriate than conventional FC in studying neuropsychiatric disorders whose pathological mechanisms were unclear ( Jiang et al., 2019 ). We found that DC and VMHC are physiologically meaningful and beneficial in understanding the underlying mechanism of SZ, DC- and VMHC-based features can distinguish SZ patients from HCs, in agreement with other studies ( de Filippis et al., 2019 ; Liu et al., 2018 ; Shan et al., 2021 ; Shi et al., 2021a ; Tang et al., 2019 ; Zang et al., 2021 ).…”
Section: Discussionsupporting
confidence: 92%
“…DC, a data-derived measurement method, measures the FC strengths across the entire brain at a voxel level and may proxy the global brain activity synchronizations or FC density ( Buckner et al., 2009 ; Li et al., 2019b ). VMHC reflects the homotopic FC between the two hemispheres by determining the correlation coefficient between voxel and the contralateral hemisphere's mirror voxel ( Lu et al., 2021 ; Shan et al., 2021 ). The two measures do not rely on prior information about the target brain regions.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations